Growth kinetic and composition of the interfacial layer for RF sputtering Al2O3 layer on germanium - Siti Kudnie, Sahari; Muhammad, Kashif; Norsuzailina, Mohamed Sutan; Zaidi, Embong; Nik Amni Fathi, Nik Zaini Fathi; Azrul Azlan, Hamzah; Rohana, Sapawi; Burhanuddin, Yeop Majlis; Ibrahim, Ahmad (Emerald Publishing Limited, 2017)
Purpose – The quality of GeOx–Ge interface and the equivalent oxide thickness (EOT) are the main issues in fabricating high-k/Ge gate stack due to the low-k of GeOx interfacial layer (IL). Therefore, a precise study of the formation of GeOx IL and its contribution to EOT is of utmost importance. In this study, the GeOx ILs were formed through post-oxidation annealing of sputtered Al2O3 on the Ge substrate. The purpose of this paper is to report on growth kinetics and composition of IL between Al2O3 and Ge for HCl- and HF-last Ge surface. Design/methodology/approach – After wet chemical cleaning with HCl or HF, Al2O3 was grown onto the Ge surface by RF sputtering. Thickness and composition of IL formed after post-anneal deposition at 400°C in dry oxygen ambience were evaluated as a function of deposition time by FESEM and characterized by X-ray photoelectron spectroscopy, respectively. Findings – It was observed that the composition and thickness of IL were dependent on the starting surface and an aluminum germinate-like composition was formed during RF sputtering for both HF- and HCl-last starting surface. Originality/value – The novelty of this work is to investigate the starting surface of Ge to IL growth between Al2O3/Ge that will lead to the improvement in Ge metal insulator field effect transistors (MISFETs) application